Using drawing and situated learning to teach transitional care to post-graduate residents - Fang-Yih Liaw; Yaw-Wen Chang; Yan-Di Chang; Li-Wen Shih; Po-Fang Tsai (BMC Medical Education, 2022)
Abstract Background The “draw-and-talk” technique has become popular in medical training, as it can help healthcare practitioners develop empathic understanding of patients and contribute to personal transformation. We adopted this method to make the teaching of transitional care planning more relevant to post-graduate residents undergoing their internal medicine training at a medical center in Taiwan. Methods Before the conventional lecture on discharge planning, trainees were invited to draw their “home” and “life as older adults” and share their drawings with others. Subsequently, they were guided to consider whether their home would be livable if they either had a disability or were old. The drawings and narratives were analyzed thematically, and feedback on the session was collected. Results Trainees were initially of the opinion that they did not have any role in discharge planning. However, the emphasis on the self-experience of drawing and the thematic use of “home” and “elderly life” led to reflective discussions about post-discharge care. The session provoked constructive self-reflection and meta-cognitive awareness and encouraged residents to actively participate in transition care plans. Response to the draw-and-talk session was overwhelmingly favorable. Conclusions Post-graduate residents in Taiwan conventionally do not have much interest or autonomy regarding their patients’ lives outside the hospital. The use of drawing and reflection is a simple and inexpensive method to contextualize discharge planning in participants’ real lives, engage them in actively visualizing the healthcare needs of older adults and patients with disability, and initiate thinking about the impact of discharge preparations, follow-up care, and barriers to care at home. Draw-and-talk might be helpful in improving residents’ knowledge and empathy toward patients preparing for discharge, which is crucial for the quality of transitional care.